Low-dimensional nanomaterials as an emerging platform for cancer diagnosis and therapy - Cui, Fengzhi; Liu, Jianhua; Zhang, Tianqi; Pang, Siwen; Yu, Haijia; Xu, Nannan (Frontiers in Bioengineering and Biotechnology, 2023)
The burden of cancer is increasing, being widely recognized as one of the main reasons for deaths among humans. Despite the tremendous efforts that have been made worldwide to stem the progression and metastasis of cancer, morbidity and mortality in malignant tumors have been clearly rising and threatening human health. In recent years, nanomedicine has come to occupy an increasingly important position in precision oncotherapy, which improves the diagnosis, treatment, and long-term prognosis of cancer. In particular, LDNs with distinctive physicochemical capabilities have provided great potential for advanced biomedical applications, attributed to their large surface area, abundant surface binding sites, and good cellular permeation properties. In addition, LDNs can integrate CT/MR/US/PAI and PTT/PDT/CDT/NDDS into a multimodal theranostic nanoplatform, enabling targeted therapy and efficacy assessments for cancer. This review attempts to concisely summarize the classification and major properties of LDNs. Simultaneously, we particularly emphasize their applications in the imaging, diagnosis, and treatment of cancerous diseases.